Un comité de révision des erreurs reliées aux médicaments - Pepin, Jocelyne; Blais, Lucie; Ehrler, Antoinette (Pharmactuel, 2015)
Résumé Un comité de révision des erreurs reliées aux médicaments a été mis en place à l’automne 1999, à l’Hôpital Général Juif. Le comité a pour mandat de compiler et de réviser tous les rapports d’incidents reçus, de conscientiser le personnel hospitalier, de faire des recommandations quant aux changements nécessaires à une utilisation plus sécuritaire des médicaments dans le centre. Le comité a d’abord instauré un système de classification des rapports d’incidents par type de médicaments ciblés, type d’erreurs et degré de sévérité. Abstract A committee to review medication-related errors was set up in the fall of 1999 at the Jewish General Hospital. The committee was mandated to compile and review all medication error reports, sensitize the staff and make recommendations regarding the changes necessary for the safer use of medications in the hospital. It first set up a system to classify reports according to medication, type of error and degree of severity. Following this classification, several interventions were carried out with varying success: • publication of leaflets • posted notices • changes to the nurse’s electronic medication administration record or to the computer system of the pharmacy • information sessions with professionals in the hospital • development of preprinted prescriptions • standardization of the use of high-risk medications • imposition of additional restrictions on prescriptions • physical changes to care units and pharmacy department • interventions with pharmaceutical companies The overall effect of these activities was to help improve safety in medication management in the hospital.